NUVOLE DI PUNTI - FRA SCANSIONE LASER E IMAGING DI PROSSIMITà€ QUALCHE CONSIDERAZIONE E RIFLESSIONE - Colombo, Luigi (GEOmedia, 2016)
The article deals with the automatic survey techniques which collect point clouds over the objects of interest. It ranges from laser scanning to survey for images, that is having meaningful awakenings through the proximity aerial survey after the advent of Unmanned Aircraft Systems. Assessments regarding the aim of application, the advantages-disadvantages of processes and the necessary technological support about telematics and information technology, complement the benchmarking.